Surface-Functionalizing Strategies for Multiplexed Molecular Biosensing: Developments Powered by Advancements in Nanotechnologies - Shangjie Zou; Guangdun Peng; Zhiqiang Ma (Nanomaterials)
Multiplexed biosensing methods for simultaneously detecting multiple biomolecules are important for investigating biological mechanisms associated with physiological processes, developing applications in life sciences, and conducting medical tests. The development of biosensors, especially those advanced biosensors with multiplexing potentials, strongly depends on advancements in nanotechnologies, including the nano-coating of thin films, micro–nano 3D structures, and nanotags for signal generation. Surface functionalization is a critical process for biosensing applications, one which enables the immobilization of biological probes or other structures that assist in the capturing of biomolecules. During this functionalizing process, nanomaterials can either be the objects of surface modification or the materials used to modify other base surfaces. These surface-functionalizing strategies, involving the coordination of sensor structures and materials, as well as the associated modifying methods, are largely determinative in the performance of biosensing applications. This review introduces the current studies on biosensors with multiplexing potentials and focuses specifically on the roles of nanomaterials in the design and functionalization of these biosensors. A detailed description of the paradigms used for method selection has been set forth to assist understanding and accelerate the application of novel nanotechnologies in the development of biosensors.